The Impact Of Modern Retail On Traditional Shops: A Case Study In Wonokerto - Dea Syakiroh Maghfirotun Nisa’; Hendri Hermawan Adinugraha (Jurnal Ilmiah Bisnis Digital, 2024)
Initially, the modern retail business mainly focused on major cities in Indonesia. However, with technological advancements and economic growth, modern retail has now reached the countryside. In many strategic places, such as Wonokerto Sub-district, for example, several modern retail outlets such as Alfamart and Indomaret have been established. The presence of these ultramodern retailers has had a significant impact on the girding of traditional retailers. Grocery store owners such as Mr. Supri and Mrs. Yatin have experienced a decrease in turnover as many consumers have switched to modern retail. However, it is not all bad news for traditional retailers. Some of them are suitable to survive in the face of decreasingly fierce business competition. This exploration aims to understand the competition between ultramodern and traditional retailers, focusing on a case study of Alfamart and Indomaret against girding small shops in Wonokerto District, Pekalongan Regency. The research used a field method, which involved interviews with four grocery store owners, the store heads of Alfamart and Indomaret, as well as documentation collection. The data collected was analysed qualitatively with an inductive approach, where specific facts are drawn to make generalizations. From the exploration results, it's concluded that the actuality of Alfamart and Indomaret in Wonokerto Subdistrict has an impact on the development of small shops in the vicinity. However, competition between minimarkets and small shops takes place in accordance with applicable regulations, without violation of the law or the president's rules. The process of establishing minimarkets in Wonokerto Subdistrict has also complied with established procedures.